Karakteristik Religius Kultur Kampus Dalam Keseharian Mahasiswa Universitas Pendidikan Indonesia - Dini Nurjannah; Sofi Wulan Sari; Tanti Oktaviani; Agus Fakhruddin (Edudeena: Journal of Islamic Religious Education)
Abstract: Various religious activities are a mandatory aspect for all Muslim students at Universitas Pendidikan Indonesia (UPI) to embody the "religious" motto in the UPI profile. These activities serve as a means of educational development and religious reinforcement, becoming the center for Islamic education. The aim of this study is to analyze the impact of students' religious activities on the religiosity of UPI students in their daily lives. Key supporting activities include PAI tutorials, SPAI, and BBQ/BTQ. The research was conducted using a qualitative approach with a descriptive method. The participants of this study were Muslim students of UPI. Data collection techniques included questionnaires distributed among the students, and data analysis involved data reduction, data presentation, and conclusion drawing. The findings focused on the religious characteristics possessed by the students and their habits that reflect religious traits. The results indicated the success of religious activities in fostering a religious atmosphere in the daily life of UPI students. Students regularly practice pious deeds, both ritual and social, as well as environmental, demonstrating that UPI students exhibit good morals and possess religious characteristics.